Sistem Pendukung Keputusan Menentukan Pengangguran Untuk Pembinaan Kerja Pada Desa Menggunakan Metode (SAW) - ratnasari, Mei; Prasasti, Ian Harum (Publikasi Indonesia, 2021)
Social assistance for the community is the main task and mission of the government to improve the welfare of the nation and state. Therefore, the government continues to innovate about social assistance in the community, especially in Gumukrejo Village. In running the social assistance program, the local government and Gumukrejo Village work together to minimize the distribution of assistance that is not on target. This research was motivated when the author conducted observations and interviewed one of the Gumukrejo Village staff, it was concluded that the lack of knowledge of residents about the conditions for providing assistance and the absence of definite criteria from Gumukrejo Village when providing assistance, therefore, a decision support system was needed to assist village staff in determining recipients of social assistance, a Decision Support System application was made about Determining recipients of social assistance based on 4 criteria. Namely Income, Marital Status, Number of dependents, and age. The decision support system method used is the Simple Additive Weighting (SAW) method. Where the results of this decision support system are in the form of ranking prospective recipients of social assistance according to the final value of the results obtained. With the creation of this social assistance recipient decision support system, it is hoped that it will be able to facilitate the distribution of aid recipients in Gumukrejo Village and in other villages.